Response to oxidative stress induced by cadmium and copper in tobacco plants (Nicotiana tabacum) engineered with the trehalose-6-phosphate synthase gene (AtTPS1) - Martins, Luísa Louro (2014)
The response of tobacco plants genetically engineered with the AtTPS1 gene to stress induced by excess Cu and Cd was evaluated in hydroponic solution (100 and 400 lM Cu and 50 and 200 lM Cd) after a 48 h exposure. Two transgenic lines, transformed with the AtTPS1 (trehalose-6-phosphate synthase) gene from Arabidopsis, with different levels of trehalose-6-phosphate synthase expression (B5H, higher and B1F, lower), and a wild type (WT) were investigated. Protein content, antioxidative enzymes (CAT, POD, SOD, and APX), glucose, fructose, lipid peroxidation, hydrogen peroxide and Cd and Cu contents were determined in leaves. The two transgenic lines were differently influenced by Cd and Cu exposure as they induced a different antioxidant enzymatic defense response. B1F and B5H plants showed a better acclimation to Cd and excess Cu compared to WT. Furthermore B1F was more tolerant than B5H to Cd and excess Cu. B1F accumulated less Cd and Cu in leaves, probably due to a more efficient exclusion mechanism. Catalase was shown to be the most important enzyme in the antioxidative system of these plants.